2017
DOI: 10.4212/cjhp.v70i6.1713
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Practice in Kenya

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 3 publications
(3 reference statements)
0
20
0
Order By: Relevance
“…Community human drug stores are mostly operated by pharmaceutical technicians who are responsible for dispensing antibiotics, while only a few, mostly large, drug stores have a registered pharmacist (holding a bachelor’s degree in pharmacy). Both pharmaceutical technicians and pharmacists are able to sell, but not prescribe antibiotics in Kenya [11]. Veterinary drugs stores are mostly operated by animal health technicians (also referred to as para-veterinarians) with just a few operated by veterinarians.…”
Section: Methodsmentioning
confidence: 99%
“…Community human drug stores are mostly operated by pharmaceutical technicians who are responsible for dispensing antibiotics, while only a few, mostly large, drug stores have a registered pharmacist (holding a bachelor’s degree in pharmacy). Both pharmaceutical technicians and pharmacists are able to sell, but not prescribe antibiotics in Kenya [11]. Veterinary drugs stores are mostly operated by animal health technicians (also referred to as para-veterinarians) with just a few operated by veterinarians.…”
Section: Methodsmentioning
confidence: 99%
“…The delivery of PrEP at private pharmacies in Africa is feasible and within the domain of care for pharmacy providers. PrEP delivery has relatively few necessary components – HIV testing, counselling (on PrEP adherence and HIV risk reduction), PrEP prescribing (including assessment of acute HIV infection and PrEP side effects) and drug dispensing (Figure 1) [11] – all of which can be done by pharmacists or pharmaceutical technologists in low‐resource settings (especially with remote clinician oversight, like the US model) [12]. Already, many private pharmacies counsel clients on the importance of adherence to medications for hypertension and diabetes, as well as the importance of condom use for pregnancy and sexually transmitted infection prevention.…”
Section: Figurementioning
confidence: 99%
“…Pharmacies can offer free, subsidized, or fully fee-for-service care, and paying for a service could result in greater sustained consumer engagement. The core components of PrEPincluding HIV testing, adherence and risk reduction counseling, assessment of side effects, and provision of refills [20,21] are all within the scope of practice for pharmacy professionals [22,23]. In the US, one model has demonstrated that PrEP can be provided completely by pharmacists, with oversight by a remote physician [24,25].…”
Section: Introductionmentioning
confidence: 99%